AGE AND OCULAR MANIFESTATIONS IN HIV PATIENTS AT VCT POLYCLINIC, PROF. DR. IGNG NGOERAH HOSPITAL, DENPASAR PERIOD JUNE 2020 TO APRIL 2023: A HOSPITAL BASED ANALYTIC RETROSPECTIVE STUDY - Pramanto, Adji; Juliari, I Gusti Ayu Made; Pramita, Ida Ayu Ary (Universitas Pahlawan Tuanku Tambusai, 2024)
Ocular manifestation in HIV refers to a wide range of eye problems. The likelihood of experiencing at least one visual symptom increases with age in HIV patients. The possible explanation is that older people may be more susceptible to other health problems that can exacerbate ocular manifestations. People who have had HIV for a longer period also may experience decline in the immune function, and accumulation of chronic inflammation and damage over time therefore increasing their risk of complications. Examining the possible clinical correlation between age and ocular manifestation in HIV patients was the primary objective of the research. 159 HIV-positive Patients at Prof. IGNG. Ngoerah Central General Hospital Voluntary Counseling and Testing (VCT) Clinic in Denpasar, Bali were examined for ocular-related complaints between June 2020 and April 2023 as part of this hospital-based analytic retrospective study. The research found no statistically significant correlation between age and the occurrence of ocular symptoms (p = 0.276). However, the percentage of HIV patients that have ocular manifestations increase along with older age group. Age and ocular manifestation did not correlate significantly in the HIV patient population. To further understand the relationship between age, length of HIV infection, and the onset of ocular symptoms, further research is required.